Overview of the Implementation of the Disaster Preparedness School Program at the Sukma Bangsa Lhokseumawe School - Yusrawati; Mawar Hayati; Fitriana Dewi (Proceedings of Malikussaleh International Conference on Health and Disaster Medicine (MICOHEDMED), 2024)
The increasing incidence of natural disasters caused by global warming and climate change has given rise to a greater need for disaster preparedness. One important aspect of this preparedness is the protection of children and their education, especially in the school environment. Education has an important role in equipping students with the knowledge and skills to face emergency disaster situations. Schools, as educational and community centers, have a central role in preparing children to face the threat of disaster. Therefore, the Disaster Preparedness School Program (SSB) is a relevant solution to mitigate disaster risks and protect children and their education. A disaster safe school/madrasah is a school/madrasah that implements standard facilities and infrastructure as well as a culture that is able to protect the school community and the surrounding environment from the dangers of disasters. The SSB program has spread widely in Indonesia, but its implementation still raises several problems that require further research. This research problem includes factors that influence its implementation, challenges in implementation and the impact of implementing this program on school residents. The aim of this research is to describe the implementation of the SSB Program at the Sukma Bangsa Lhokseumawe School which focuses on problems that require analysis of the factors that influence them. The population of this research is all Sukma Bangsa Lhokseumawe school officials, namely students, school principals, teacher councils, education staff and school committees with a total population of 800 people, a sample of 270 respondents. The data collection technique uses a questionnaire with 15 statements measured using a Likert scale. Based on the univariate test, the results show that the implementation of the Disaster Preparedness School Program is still very low 96 respondents were less exposed to the implementation of the SSB program in schools, only 90 were in the good category. Analysis using Multiple regression shows that there is a significant relationship between the respondent categories and their perceptions of the implementation of the SSB program, the R obtained in data processing is 0.620. And according to statistical calculations based on these figures, the influence of the independent variable on the dependent variable is 62%. The conclusion of this research shows that further outreach regarding the SSB program in the school environment is still needed. improve the implementation of this program and assist the government and related organizations in developing more effective strategies in implementing disaster preparedness school programs.